The Behaviour of the Commodity market during 1997-2012: Evidence from the London Metal Exchange - Tang, Dayle (2013)
Using time-series model, the investigation seeks the different factors that affects the fluctuations of the copper market, specifically the London Metal Exchange. By investigating two periods, 1997-2002 and 2003-2012, it will highlight the different and similar factors which are considered to affect copper prices. There is the addition to observe the correlation coefficient of other commodity prices with copper prices. It is consider to have minimal correlation, however this could have change after the millennium year. The conclusion will indicate the similarities and difference of the two results, and identify any insignificant factors that will be explained.